Through the Back Door The Black Market in Poland 1944-1989 - Kochanowski, Jerzy (Studies in Contemporary History, 2017)
This book analyzes the history of the black market in Poland before the 1940s and the development of black-market phenomena in post-war Poland. The author evaluates the interrelation between black-market phenomena and historical and geographical conditions. At first, the black market stabilized the system by making it more flexible and creating a margin of freedom, albeit in the short term. In the long run, the informal economic activities of the people ran counter to and undermined the official ideology of the state. The author concludes that in post-war Poland, owing to a singular coincidence of historical, political, economic and social factors, the second economy had its own unique character and an endemic presence that loomed large in the Soviet Bloc.